Meningkatkan Keterampilan Abad 21 Dengan Model Project Based Learning Pada Pembelajaran Pendidikan Agama Islam Di SMK Muhammadiyah 5 - Maimunah, Maimunah; Jannah, Nur (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
The weak ability of critical thinking and problem solving skills, which are important parts of 21st century skills, requires innovation in the learning process, especially in Islamic religious education (PAI), so that students can face global challenges in an adaptive way. This study aims to reveal the improvement of students' 21st century skills through the application of project-based learning (PjBL) model in Islamic education subjects at SMK Muhammadiyah 5 Jember. This research approach is qualitative with the type of phenomenology, where data is obtained through observation, interviews, and documentation. The results showed that the application of PjBL in PAI learning was able to significantly improve students' 4C (Critical Thinking, Communication, Collaboration, and Creativity) skills. This model provides a participatory space that encourages students to think critically, work together effectively, communicate actively, and foster creativity in understanding and practicing Islamic values. Thus, Project Based Learning proves to be a relevant and transformative approach to improve the quality of PAI learning in the 21st century era.